A comparison of the effectiveness of intralesional tranexamic acid against platelet-rich plasma in the treatment of melasma - Karthikeyan, Manasha; Kumar, Govardhan Jagadeesh; Radhakrishnan, Indradevi (International Journal of Research in Dermatology, 2024)
Background: Melasma, derived from the Greek word "melas" meaning "black", manifests as an acquired, more or less symmetrical hypermelanosis of sun-exposed skin. This study aimed to compare and evaluate the efficacy and safety of intradermal injection of tranexamic acid and platelet-rich plasma in treating various types of melasma. Methods: Conducted from June 2022 to December 2023 at the outpatient department of dermatology, Sri Lakshmi Narayana institute of medical sciences, Puducherry, this split-face prospective study involved 40 melasma cases. Tranexamic acid (4 mg/ml) was intradermally injected into the right side of the face, while PRP was injected into the left side. Improvement was assessed using the modified Melasma area severity index (MASI) grading system and dermoscopy, measuring disease severity and percentage of improvement before and after therapy on both sides of the face. Results: The study comprised predominantly females (80%) aged 20 to 30 years (50%), followed by those aged 30 to 40 years (35%). Most cases (93%) exhibited a gradual onset, with centrofacial (52.5%) and malar (37.5%) patterns being predominant. Mixed pattern (67.5%) was common. Pre-treatment mean MASI scores for tranexamic acid and PRP sides were 7.54 and 6.92, respectively, with post-treatment scores of 4.6 and 2.83, respectively. Conclusions: Intradermal PRP demonstrated significantly superior efficacy over intradermal tranexamic acid in managing melasma, particularly in the longer term. Thus, PRP, coupled with good compliance, may substantially reduce the disease burden compared to conventional tranexamic acid treatment.